Iron sulfide compound and preparation method thereof
By conducting hydrothermal reaction in the presence of surfactant and combining sonication and centrifugal treatment, the problems of low purity and low yield of ferric sulfide compounds in the prior art were solved, and high purity and high crystallinity ferric sulfide compounds were prepared, which were suitable for oil well tube corrosion research.
Patent Information
- Application Number
- CN202510587819.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-08-15
AI Technical Summary
The prior art has problems of low purity, imbalance in energy consumption and low yield when synthesizing iron sulfide compounds. Especially in hydrothermal synthesis, it is difficult to prepare high purity and high crystallinity iron sulfide compounds.
Hydrothermal reaction was carried out in the presence of surfactant, combined with sonication and centrifugation, the heating rate and end-point temperature of the hydrothermal reaction were controlled, and iron sulfhydryl compound was obtained through insulation treatment and multiple washings.
High-purity and high yield sulfide compounds were prepared, with high crystallinity and similar crystal structures to single-crystal pyrite and pyrite in natural environment, and are suitable for oil well tube corrosion research.
Smart Images

Figure CN120483266A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ferric sulfide compound synthesis, and in particular to a ferric sulfide compound and a preparation method thereof. Background Art
[0002] With the development of sour oil and gas fields and the continuous extension of oil and gas extraction to deep and ultra-deep formations, a large amount of H2S gas is accompanied by the extraction process. In a humid environment, the presence of H2S gas can cause severe uniform corrosion and pitting perforation of the pipe. Studies have shown that the corrosion products produced by oil casing in an H2S environment have a significant impact on its subsequent corrosion process. In a humid H2S environment, the corrosion products produced on the surface of the oil casing are often non-stoichiometric sulfide compounds, including maquinosite, pyrrhotite, pyrite, meteoric iron and marcasite. Some forms of sulfide compounds have a certain inhibitory effect on the corrosion process. Their density and crystal type may be the reason for their protective properties. In order to explore the effect of a single sulfide compound on the corrosion of oil well pipes, synthesizing pure-phase sulfide compounds has become a possible approach.
[0003] Currently, the main methods for synthesizing ferrous sulfide compounds include: high-temperature solid-phase synthesis, mechanical ball milling, chemical vapor deposition, and hydrothermal synthesis. Among them, the mechanical ball milling method is limited by the size of the ball mill, has a low yield, and is somewhat dangerous; the high-temperature solid-phase synthesis method requires a high test temperature during the synthesis process, and the synthesized ferrous sulfide compounds do not have a regular crystal form; the ferrous sulfide compounds synthesized by chemical vapor deposition often contain ferrous sulfide compounds of other crystal forms.
[0004] The hydrothermal synthesis method is simple to operate and highly efficient, and the resulting ferrosulfide compounds have a crystal structure similar to those produced naturally. For example, CN116161708A discloses a hydrothermal method for synthesizing pyrite. This method involves using Fe(NO3)3·9H2O as a starting solution, adding KOH for aging to produce goethite. The goethite is then reacted with sodium sulfide at 50°C for three days to produce pyrite. Finally, hydrochloric acid is added to dissolve and remove impurities to produce the pyrite product. However, this method still suffers from low product purity and an imbalance between energy consumption and efficiency. Summary of the Invention
[0005] The purpose of the present invention is to provide a process method which has the advantages of simple operation and high synthesis efficiency while ensuring the preparation of high-purity ferrosulphide compounds.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing an iron sulfide compound, the method comprising:
[0007] (1) in the presence of a surfactant, subjecting a mixed solution containing a sulfur source and an iron source to a hydrothermal reaction to obtain a first material;
[0008] The heating rate of the hydrothermal reaction is 4-7°C / min, and the heating end temperature is 120-220°C;
[0009] (2) subjecting the first material to heat preservation treatment to obtain a second material;
[0010] The heat preservation time is 24-48h;
[0011] (3) subjecting the second material to ultrasonic treatment and centrifugation in sequence to obtain a sulfide iron compound;
[0012] The ultrasonic treatment time is ≮10 min; the centrifugal treatment conditions include: a rotation speed of 6000-9000 rpm and a time of 8-20 min.
[0013] Preferably, in step (1), the weight ratio of the sulfur source to the iron source is 1:0.3-0.9.
[0014] Preferably, in step (1), the heating rate of the hydrothermal reaction is 4-6°C / min, and the heating end point temperature is 200-220°C.
[0015] Preferably, in step (2), the heat preservation treatment time is 24-48 hours.
[0016] Preferably, in step (1), the sulfur source is thiourea and / or sodium sulfide.
[0017] Preferably, in step (1), the iron source is selected from at least one of ferrous chloride, ferrous sulfate and ferric chloride.
[0018] Preferably, in step (1), the surfactant is selected from at least one of polyvinylpyrrolidone, cetyltrimethylammonium bromide and thioacetamide.
[0019] Preferably, in step (3), the power of the ultrasonic treatment is 100-200W.
[0020] Preferably, in step (3), the method further comprises: drying the product after the centrifugal treatment.
[0021] Preferably, the drying conditions include: a temperature of 60-90° C. and a time of 4-6 hours.
[0022] The second aspect of the present invention provides an iron sulfide compound prepared by the method described in the first aspect.
[0023] Through the above technical solution, the present invention has at least the following advantages over the prior art:
[0024] (1) The preparation method of the ferrous sulfide compound provided by the present invention has a simple process, is easy to implement and control, and has low cost.
[0025] (2) The ferrosulfide compound prepared by the method provided by the present invention has high crystallinity and is relatively close to the crystal structure of single crystal pyrite and pyrrhotite in natural environment; and the ferrosulfide compound has high purity and high yield and can be produced in batches. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the XRD pattern of the iron sulfide compound of Example 1 of the present invention;
[0027] Figure 2 is a SEM image of the ferrous sulfide compound of Example 1 of the present invention;
[0028] Figure 3 is the XRD pattern of the iron sulfide compound of Example 2 of the present invention;
[0029] Figure 4 is the XRD pattern of the ferrous sulfide compound of Example 3 of the present invention;
[0030] Figure 5 is the XRD pattern of the iron sulfide compound of Example 4 of the present invention;
[0031] Figure 6 is a SEM image of the ferrous sulfide compound of Example 4 of the present invention;
[0032] Figure 7 is the XRD pattern of the iron sulfide compound of Example 5 of the present invention;
[0033] Figure 8 is the XRD pattern of the iron sulfide compound of Example 6 of the present invention;
[0034] Figure 9 is the XRD pattern of the iron sulfide compound of Example 7 of the present invention;
[0035] Figure 10 is the XRD pattern of the iron sulfide compound of Comparative Example 1 of the present invention;
[0036] Figure 11 It is the XRD pattern of the iron sulfide compound of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0037] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0038] As mentioned above, the first aspect of the present invention provides a method for preparing an iron sulfide compound, the method comprising:
[0039] (1) in the presence of a surfactant, subjecting a mixed solution containing a sulfur source and an iron source to a hydrothermal reaction to obtain a first material;
[0040] The heating rate of the hydrothermal reaction is 4-7°C / min, and the heating end temperature is 120-220°C;
[0041] (2) subjecting the first material to heat preservation treatment to obtain a second material;
[0042] The heat preservation time is 24-48h;
[0043] (3) subjecting the second material to ultrasonic treatment and centrifugation in sequence to obtain a sulfide iron compound;
[0044] The ultrasonic treatment time is ≮10 min; the centrifugal treatment conditions include: a rotation speed of 6000-9000 rpm and a time of 8-20 min.
[0045] Preferably, in step (1), the weight ratio of the sulfur source to the iron source is 1:0.3-0.9. The inventors have found that under this preferred embodiment, the technical solution provided by the present invention can obtain ferrosulfide compounds with higher purity and higher yield.
[0046] Preferably, in step (1), the heating rate of the hydrothermal reaction is 4-6° C. / min, and the heating end temperature is 200-220° C. In this preferred embodiment, the technical solution provided by the present invention can obtain ferrosulfide compounds with higher purity and higher yield.
[0047] Preferably, in step (2), the heat preservation treatment time is 24-48 hours.
[0048] Preferably, in step (1), the sulfur source is thiourea and / or sodium sulfide.
[0049] According to a preferred embodiment, in step (1), the mixed solution containing the sulfur source and the iron source is obtained by ultrasonically dissolving the sulfur source and the iron source in the presence of a solvent.
[0050] The present invention has no particular limitation on the time of ultrasonic dissolution, as long as the sulfur source and the iron source are fully dissolved in the solvent. For example, the time of ultrasonic dissolution is 8-15 minutes.
[0051] Preferably, in step (1), the solvent in the mixed liquid is water.
[0052] Preferably, in step (1), the iron source is selected from at least one of ferrous chloride, ferrous sulfate and ferric chloride.
[0053] Preferably, in step (1), the surfactant is selected from at least one of polyvinylpyrrolidone, cetyltrimethylammonium bromide and thioacetamide.
[0054] Preferably, in step (3), the power of the ultrasonic treatment is 100-200W.
[0055] Preferably, in step (3), the method further comprises: drying the product after the centrifugal treatment.
[0056] Preferably, the drying conditions include: a temperature of 60-90° C. and a time of 4-6 hours.
[0057] The method of the present invention further includes stirring, washing, and other operations. For example, the material obtained by the centrifugation is washed with deionized water and anhydrous ethanol, and then subjected to ultrasonic treatment and centrifugation again for multiple cycles. The supernatant is discarded, and the product is then dried to obtain the iron sulfide compound. The present invention will not be described in detail here, and those skilled in the art should not be construed as limiting the present invention.
[0058] As mentioned above, the second aspect of the present invention provides an iron sulfide compound prepared by the method described in the first aspect.
[0059] Preferably, the ferrous sulfide compounds include pyrrhotite and pyrite.
[0060] Preferably, the average particle diameter of the iron sulfide compound is 2-7 μm, preferably 3-5 μm.
[0061] Preferably, the purity of the ferric sulfide compound is ≥80 wt%, more preferably ≥91 wt%, and most preferably 92-98 wt%.
[0062] Preferably, the yield of the ferric sulfide compound is ≥81 wt%, more preferably 86-92 wt%.
[0063] The present invention will be described in detail below by way of examples. In the following examples, the reagents and instruments used are all commercially available.
[0064] In the following examples, the test methods and calculation formulas involved include:
[0065] XRD pattern: obtained by Bruker D8 Focus X-ray diffractometer test;
[0066] SEM image: obtained by KYKY-EM6200 field emission scanning electron microscope test;
[0067] Purity (wt%) = target product (iron sulfide compound) / total mass of product × 100%;
[0068] Yield (wt%) = actual yield / theoretical yield × 100%.
[0069] Example 1
[0070] (1) Accurately weigh a certain amount of iron source (FeCl2·4H2O) and sulfur source, add them to 70 mL of deionized water, stir and dissolve, and ultrasonicate for 10 min to evenly disperse. After the FeCl2·4H2O and thiourea are completely dissolved, weigh 0.35 g of polyvinylpyrrolidone (PVP) and add it to the solution. Stir while ultrasonicating. After the surfactant is completely dissolved, pour the mixture into a 100 mL hydrothermal reactor.
[0071] After the hydrothermal kettle is placed in an oven, the oven temperature is set to 200° C., and the mixed liquid in the hydrothermal kettle undergoes a constant-temperature hydrothermal reaction to obtain the first material.
[0072] (2) The first material is kept warm and naturally and evenly cooled to room temperature to obtain the second material.
[0073] (3) The second material in the hydrothermal kettle was poured out, and the inner wall of the hydrothermal kettle was washed with deionized water. After natural sedimentation, the supernatant was poured out, and the remaining solution was subjected to ultrasonic treatment (power of 120 W) and centrifugation (speed of 7000 rpm, time for 10 min). The product after centrifugation was washed again with deionized water and anhydrous ethanol, and ultrasonic treatment and centrifugation were repeated again. This process was repeated 2-3 times;
[0074] The centrifuged product was dried in a vacuum oven at 60° C. for 6 h to obtain an iron sulfide compound.
[0075] The raw material ratio, condition parameters and product parameters of this example are shown in Table 1.
[0076] The remaining examples were prepared using the same preparation method as Example 1, except that the raw material ratios and condition parameters were different, resulting in ferrosulfide compounds with different particle sizes, as shown in Table 1.
[0077] Table 1
[0078]
[0079]
[0080] Note: “Amount weight ratio” refers to the amount weight ratio of sulfur source to iron source.
[0081] Example 8
[0082] A method similar to that of Example 1 was used, except that in step (1), the amount of the sulfur source was kept unchanged, and the weight ratio of the sulfur source to the iron source in this example was adjusted to 1:1.1;
[0083] The rest of the process was the same to obtain a ferrosulfide compound, and the test showed that the average particle diameter of the ferrosulfide compound was 5 μm.
[0084] Example 9
[0085] A method similar to that of Example 1 was used, except that in step (1), the heating rate of the hydrothermal reaction in this example was adjusted to 7°C / min, and the heating end temperature was adjusted to 180°C;
[0086] The rest of the process was the same to obtain a ferrous sulfide compound, and the test showed that the average particle diameter of the ferrous sulfide compound was 7 μm.
[0087] Comparative Example 1
[0088] A method similar to that of Example 1 was used, except that in step (1), the heating rate of the hydrothermal reaction in this example was adjusted to 10°C / min, and the heating end point temperature was adjusted to 250°C;
[0089] The rest of the steps were the same to obtain a ferrosulfide compound, and the test showed that the average particle diameter of the ferrosulfide compound was 6 μm.
[0090] Comparative Example 2
[0091] A method similar to that of Example 1 was used, except that in step (2), the centrifugal treatment conditions in this example were adjusted to: a rotation speed of 5000 rpm and a time of 25 min;
[0092] The rest of the steps were the same to obtain a ferrosulfide compound, and the test showed that the average particle diameter of the ferrosulfide compound was 6 μm.
[0093] Test Case
[0094] The purity and yield of the ferrous sulfide compound obtained in the example were tested, and the test results are shown in Table 2.
[0095] Table 2
[0096] Purity (wt%) Yield (wt%) Example 1 96.5 87.5 Example 2 95.8 89.3 Example 3 92.3 86.5 Example 4 91.2 91.3 Example 5 97.1 81.7 Example 6 95.4 85.5 Example 7 93.5 83.7 Example 8 84.2 80.6 Example 9 88.5 83.2 Comparative Example 1 76.9 70.1 Comparative Example 2 75.3 68.5
[0097] The present invention is exemplified in Figure 1 The XRD pattern of the iron sulfide compound of Example 1 is provided in Figure 2 The SEM image of the iron sulfide compound of Example 1 is provided in Figure 1 and Figure 2 It can be seen that the pyrite compound prepared in Example 1 is pure-phase pyrrhotite, and no impurity peaks of other pyrite compounds appear in the pyrrhotite. Moreover, the synthesized pyrrhotite has a typical hexagonal lamellar crystal form.
[0098] The present invention is exemplified in Figure 3 The XRD pattern of the iron sulfide compound of Example 2 is provided in Figure 3 It can be seen that pure-phase pyrrhotite was successfully prepared in Example 2. The pyrrhotite prepared in this example was also relatively pure, and no other impurity peaks appeared in the XRD pattern.
[0099] The present invention is exemplified in Figure 4 The XRD pattern of the iron sulfide compound of Example 3 is provided in Figure 4 It can be seen that pure-phase pyrrhotite was successfully prepared in Example 3. The pyrrhotite was also relatively pure, and no other impurity peaks appeared in the XRD pattern.
[0100] The present invention is exemplified in Figure 5 The XRD pattern of the iron sulfide compound of Example 4 is provided in Figure 6 The SEM image of the iron sulfide compound of Example 4 is provided in Figure 5 and Figure 6 It can be seen that the ferrous sulfide compound prepared in this example is relatively pure pyrite, does not have the impurity peaks of other ferrous sulfide compounds, and has a typical cubic crystal structure of pyrite.
[0101] The present invention is exemplified in Figure 7 The XRD pattern of the iron sulfide compound of Example 5 is provided in Figure 7 It can be seen that the ferrous sulfide compound prepared in this embodiment is pyrite, which is also relatively pure and does not contain impurity peaks of other ferrous sulfide compounds.
[0102] The present invention is exemplified in Figure 8 The XRD pattern of the iron sulfide compound of Example 6 is provided in Figure 8 It can be seen that the ferrous sulfide compound prepared in this embodiment is pyrite, which is also relatively pure and does not contain impurity peaks of other ferrous sulfide compounds.
[0103] The present invention is exemplified in Figure 9 The XRD pattern of the iron sulfide compound of Example 7 is provided in Figure 9It can be seen that the ferrous sulfide compound prepared in this embodiment is pyrite, which is also relatively pure and does not contain impurity peaks of other ferrous sulfide compounds.
[0104] The present invention is exemplified in Figure 10 The XRD pattern of the iron sulfide compound of Comparative Example 1 is provided in Figure 10 It can be seen that there are many impurity peaks in the figure, mainly marcasite. The impurity products will affect the subsequent study of the effect of single crystal ferrous sulfide compounds on hydrogen sulfide corrosion.
[0105] The present invention is exemplified in Figure 11 The XRD pattern of the iron sulfide compound of Comparative Example 2 is provided in Figure 11 It can be seen that there are many impurity peaks in the figure, mainly marcasite. The impurity products will affect the subsequent study of the effect of single crystal ferrous sulfide compounds on hydrogen sulfide corrosion.
[0106] From the above results, it can be seen that the present invention, by controlling the condition parameters of the hydrothermal reaction and post-treatment, can produce a sulfide iron compound with high crystallinity and a crystal structure similar to that of single-crystal pyrite and pyrrhotite in a natural environment, and the sulfide iron compound has high purity and high yield.
[0107] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A method for preparing a ferrous sulfide compound, characterized in that: The method includes: (1) in the presence of a surfactant, subjecting a mixed solution containing a sulfur source and an iron source to a hydrothermal reaction to obtain a first material; The heating rate of the hydrothermal reaction is 4-7°C / min, and the heating end temperature is 120-220°C; (2) subjecting the first material to heat preservation treatment to obtain a second material; (3) subjecting the second material to ultrasonic treatment and centrifugation in sequence to obtain a sulfide iron compound; The ultrasonic treatment time is ≮10 min; the centrifugal treatment conditions include: a rotation speed of 6000-9000 rpm and a time of 8-20 min.
2. The method according to claim 1, characterized in that In step (1), the weight ratio of the sulfur source to the iron source is 1:0.3-0.
9.
3. The method according to claim 1, characterized in that In step (1), the heating rate of the hydrothermal reaction is 4-6°C / min, and the heating end temperature is 200-220°C; And / or, in step (2), the heat preservation treatment time is 24-48 hours.
4. The method according to any one of claims 1 to 3, characterized in that In step (1), the sulfur source is thiourea and / or sodium sulfide.
5. The method according to any one of claims 1 to 3, characterized in that In step (1), the iron source is selected from at least one of ferrous chloride, ferrous sulfate and ferric chloride.
6. The method according to any one of claims 1 to 3, characterized in that In step (1), the surfactant is selected from at least one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide and thioacetamide.
7. The method according to any one of claims 1 to 3, characterized in that In step (3), the power of the ultrasonic treatment is 100-200W.
8. The method according to any one of claims 1 to 3, characterized in that In step (3), the method further comprises: drying the product after the centrifugal treatment.
9. The method according to claim 8, characterized in that The drying conditions include: a temperature of 60-90° C. and a drying time of 4-6 hours.
10. The iron sulfide compound prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method for synthesizing pyrite by hydrothermal method
CN116161708A
Anode material and anode plate of lithium-iron disulfide battery and method for preparing same
CN101521279A
Method for preparing nano-micron pyrite cubic crystals under hydrothermal condition
CN103305900A
FeS nanosheet preparing method
CN105314686A
Ferrous disulfide microspheres and preparation method thereof
CN106745322A